Hasil Uji Kalibrasi Sensor Accelerometer ADXL335 - Setiawan, Iwan; Setiyono, Budi; Susilo, Tri Bagus (Transmisi, 2009)
Accelerometer is a sensor that can measure acceleration of object. This sensor can be used for till sensing detection, 3D game interface, computer’s mouse, and vehicle navigation system. Operating of this sensor need a good calibration to get parameters which determines the acceleration. This paper present result of calibration of 3 Axis ADXL335 accelerometer. Calibration of this sensor consist of 3 step testing on every axis of this sensor, sensor’s natural characteristic testing, ZeroG voltage testing, and sensor’s sensitivity testing. The result of testing ZeroG voltage and sensitivity must be compare with information from datasheet. From this testing can be concluded that the ADXL335 accelerometer has responsive output. Percentage of deviation standard is 0.257397% and the minimum is 0%. The value of ZeroG voltage from testing are 1,637390 volt for X axis, 1,638319 volt for Y axis, dan 1,736877 volt for Z axis. And the sensitivity are 0,3096 V/g for X axis, 0,3296925 V/g for Y axis, Z axis is 0,3103370 V/g. Keywords: Accelerometer, accelereration, calibration, ZeroG voltage, sensitivity.